Studi Empiris Penentu Kinerja Keuangan Perusahaan yang Diukur Dengan Pertumbuhan Laba pada Perusahaan Manufaktur yang Terdaftar di BEI - Bimawan , Fitnantyo (Akademi Akuntasi Effendiharahap, 2021)
The success of the company's financial performance can be seen from the profit growth owned by the company. So far there have been many studies on earnings growth, because profit growth is an important thing and noticed by many parties, both investors and creditors, which affect profit growth in investing their capital. This study examines the effect of institutional ownership, debt to equity ratio, liquidity, and firm size on profit growth. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange for the period 2012-2015. The sample in this study were 160 companies. The analytical tool used is Multiple Linear Regression. The results of this study indicate that the variables of institutional ownership have no effect on profit growth. Debt to Equity Ratio has no effect on profit growth. Liquidity affects earnings growth. Company size affects profit growth